Three-Dimensional Explant Platform for Studies on Choroid Plexus Epithelium - Petersen, Natalia; Torz, Lola; Jensen, Kristian H. Reveles; Hjortø, Gertrud Malene; Spiess, Katja; Rosenkilde, Mette Marie (Frontiers in Cellular Neuroscience, 2020)
The choroid plexus (CP) plays a major role in controlling entry of substances and immune cells into the brain as it forms the blood-cerebrospinal fluid (CSF) barrier in the brain ventricles. Dysregulated immune cell trafficking through the epithelial cell layer of CP is central for the pathogenesis of infectious diseases in the brain and for a number of neurodegenerative disorders. In vitro studies elucidating the function of the CP has so far been limited to monolayer culture of CP epithelial cells. In order to mimic immune cell migration across the CP barrier, a three-dimensional model would be advantageous. Here we present an in vitro platform for studies of the immune cell trafficking based on CP organoids. The organoids were generated from fragments of mouse CPs in Matrigel, where the cells formed luminal spaces and could be maintained in culture for at least 8 weeks. We demonstrate expression of the major CP markers in the organoids, including transthyretin and aquaporin 1 as well as ZO1 and ICAM-1, indicating capacity for secretion of CSF and presence of tight junctions. CP organoids displayed CP-like cell polarization and formed intact epithelial cell barrier. We also show that the expression of transthyretin, transferrin, occludin and other genes associated with various functions of CP was maintained in the organoids at similar levels as in native CP. By using dendritic cells and neutrophils, we show that the migration activity of immune cells and their interactions with CP epithelial can be monitored by microscopy. Thereby, the three-dimensional CP organoid model can be used to study the cellular and molecular mechanisms mediating immune cell migration through CP epithelium and other functions of choroid epithelial cells. We propose, this platform can potentially be used in the search for therapeutic targets and intervention strategies to improve control of substances and (immune) cell entry into the central nerve system.